45th AIAA Aerospace Sciences Meeting and Exhibit 2007
DOI: 10.2514/6.2007-1063
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Visualization of Hypersonic Flow Over Rapid Prototype Wind-Tunnel Models

Abstract: Reentry models for use in hypersonic wind tunnel tests were fabricated using a stereolithography apparatus. These models were produced in one day or less, which is a significant time savings compared to the manufacture of ceramic or metal models. The models were tested in the NASA Langley Research Center 31-Inch Mach 10 Air Tunnel. Most of the models did not survive repeated tests in the tunnel, and several failure modes of the models were identified. Planar laser-induced fluorescence (PLIF) of nitric oxide (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The flow rates were recorded by the data acquisition system at 20 Hz. One figure in the paper, as will be noted, shows much higher flow rates (up to 20 slpm) obtained in a subsequent test using a permanently installed gas supply system detailed in [22].…”
Section: Wind Tunnel Operating Conditions Mass Flow Control Andmentioning
confidence: 93%
“…The flow rates were recorded by the data acquisition system at 20 Hz. One figure in the paper, as will be noted, shows much higher flow rates (up to 20 slpm) obtained in a subsequent test using a permanently installed gas supply system detailed in [22].…”
Section: Wind Tunnel Operating Conditions Mass Flow Control Andmentioning
confidence: 93%
“…For this experiment, ViDI was used primarily for post-test visualization of the PLIF data as in Ref. 6. Figure 2 shows a comparison between two images obtained using the cone nozzle: one with the wind tunnel not operating (tunnel-off) and the other with the wind tunnel operating (tunnel-on).…”
Section: E Virtual Diagnostics Interface (Vidi)mentioning
confidence: 99%
“…In a recent experiment 6 it was demonstrated that hypersonic wind tunnel capsule models could be built rapidly, inexpensively, and with internal plumbing appropriate for seeding NO, using a stereo lithography apparatus (SLA). However, the forebody capsule heating was excessive for the materials used in that test, resulting in model degradation.…”
Section: A Test Articlementioning
confidence: 99%
See 1 more Smart Citation
“…For this experiment, ViDI was used for post-test visualization of the PLIF data as in Ref. 15. All images presented in this paper represent flow conditions along the underbody of the 1/3 scale Hyper-X forebody model.…”
Section: Planar-laser Induced Fluorescence (Plif) System and Imagementioning
confidence: 99%